2015
DOI: 10.1155/2015/623287
|View full text |Cite
|
Sign up to set email alerts
|

Trigger Points: An Anatomical Substratum

Abstract: This study aimed to bring the trapezius muscle knowledge of the locations where the accessory nerve branches enter the muscle belly to reach the motor endplates and find myofascial trigger points (MTrPs). Although anatomoclinical correlations represent a major feature of MTrP, no previous reports describing the distribution of the accessory nerve branches and their anatomical relationship with MTrP are found in the literature. Both trapezius muscles from twelve adult cadavers were carefully dissected by the au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 22 publications
2
23
0
9
Order By: Relevance
“…In fact, only the BB showed a strong interindividual heterogeneity with regard to the innervation points of the MCN in the BDs. In comparing the current findings with previous findings from other research groups, strong agreements for location and quantity of NEPs could be seen for BB, Pmin, and TZ . However, due to varying reference lengths and different anatomical landmarks, direct comparisons between studies should be viewed with caution …”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In fact, only the BB showed a strong interindividual heterogeneity with regard to the innervation points of the MCN in the BDs. In comparing the current findings with previous findings from other research groups, strong agreements for location and quantity of NEPs could be seen for BB, Pmin, and TZ . However, due to varying reference lengths and different anatomical landmarks, direct comparisons between studies should be viewed with caution …”
Section: Discussionsupporting
confidence: 66%
“…Similarly, the positioning of lidocaine injections (e.g., in chronic neck pain) based on anatomical myofascial trigger points (MTrPS) may be optimized by identifying high‐density IZs . Typically used MTrPS appear to be largely in line with NEPs rather than MPs. The differences between NEPs and MPs was shown in a study by Barbero and colleagues, who reported that, in the trapezius muscle, MTrPS and IZ did not overlap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e relationship between the entry points of nerves into the muscle belly and the myofascial trigger points has already been reported by Akamatsu et al [25,26]. Nerves are responsible for muscle contraction through the release of acetylcholine from the motor endplate.…”
Section: Discussionmentioning
confidence: 77%
“…Another important finding described in a recent study demonstrated that there may be a relationship between the entry points of the nerves to the muscle belly and the myofascial trigger points [25,26]. A detailed description of the anatomy remains one of the best ways to better understand the pathophysiology and clinical applicability of myofascial trigger points.…”
Section: Introductionmentioning
confidence: 98%